Pembuatan Brosur sebagai Media Edukasi untuk Meningkatkan Pengetahuan tentang Tumbuhan Obat bagi Masyarakat - Sari, Iza Mala Pita (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
Medicinal plants are all types of plants, either cultivated or not yet cultivated, that can be used as medicinal plants. To find out to what extent medicinal plants are known to the community in Batu Mekar Village, Lingsar District, West Lombok Regency, it is necessary to create an information media for education in the form of brochures. The aim of the research is to develop brochures as educational media to increase knowledge about medicinal plants for the public. This type of research is development research. Data collection techniques use validation sheets and readability tests. The data analysis technique used is the percentage technique. The research results showed that content/material experts had a validation score of 84% and their qualifications were very good. Linguist with a validation score of 70% and good qualifications. Display expert with a validation score of 70% and good qualifications. Meanwhile, the readability test was carried out by 20 people in the community with a score of 80% and their qualifications were very good.